Flowers and thorns in pregnancy: experiences during the COVID-19 pandemic - Maíra Rossetto; Jeane Barros de Souza; Graciela Soares Fonsêca; Vanessa Vitória Kerkhoff; Juliana Romanoski Alves e Moura (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To understand the repercussions of COVID-19 on the path of pregnancy. Method: Qualitative, participatory action research (PAR) study, based on Paulo Freire's Research Itinerary. A virtual culture circle was held in October 2020, with the participation of 12 pregnant women, living in the South and Southeast regions of Brazil. Results: In the virtual culture circle, pregnant women talked and critically reflected on two generating themes: flowers and thorns in the course of pregnancy. They meant living in the virtual culture circle as spaces for sharing experiences, welcoming and learning, among others. Conclusions: For the participants, pregnancy during the pandemic brought difficulties such as social isolation, absence from work and the university, fears, anxieties, loneliness and insecurities. However, it also improved health care, intensifying self-care and investment in family relationships.